The efficacy of benzydamine on cancer treatment-induced oral mucositis: A systematic review of randomised controlled trials - Gümüş, Dilek; Yılmaz, Zeynep; Tuğrul, Fuzuli (The European Research Journal, 2025)
Objectives: Mucositis is a well-known complication of oncological therapies, severely affecting the quality of life of patients. Benzydamine appears to be a promising option for the treatment of this condition, particularly in the management of oral mucositis. We can learn more about the potential use of benzydamine for oral mucositis by examining the available published research and what we know from clinical trials that have used this agent. This systematic review aims to evaluate the efficacy of benzydamine for the prevention and treatment of oral mucositis induced by cancer therapy through Randomized Controlled Trials. Methods: A systematic literature review was performed across seven databases. After screening, this systematic review included nine articles that had been published between 2013 and 2023. The review was conducted in accordance with the Cochrane guidelines (2023). Bias risk is assessed using the Cochrane Collaboration Risk of Bias Assessment Tool. The studies differed in the number of participants, from 26 to 120, giving a total of 593 participants analyzed. The articles in the studies used Benzydamine, herbal formulation, sodium bicarbonate, povidone-iodine, and low-level laser. Results: Results showed that benzydamine was effective to varying extents. Several studies provided statistically important improvements while others showed no statistically important variations. Conclusions: This extensive literature review and clinical study offer insight into how benzydamine may work in the management of oral mucositis.